Multiple Myopericytoma of the Face and Parotid Gland - Yun-Ik Jung (Archives of Plastic Surgery, 2012)
Myopericytoma is a benign tumor that is composed of myoid-appearing oval to spindle-shaped cells with a concentric perivascular pattern of growth. The tumor is morphologically heterogeneous and can exhibit a broad histologic spectrum. We describe a case of multiple myopericytoma occurring in the head and neck skin region with involvement of the parotid gland where it is known to occur very rarely. A 40-year-old woman noticed multiple enlarging, painless, round-shaped masses on her left cheek. The patient had experienced a similar lesion of the same area 8 years earlier which was completely excised and the pathological diagnosis was spindle cell type myoepithelioma. On a computed tomographic image, one mass involved the superficial parotid gland and was well encapsulated. Excision of the facial masses and superficial parotidectomy with facial nerve preservation were performed. A diagnosis of myopericytoma was established in light of the immunohistochemical pattern with the histopathological findings. Over the 4-year follow-up period, there was no evidence of recurrence. As many perivascular myoid neoplasms share common morphologic features with myopericytoma, we should consider the differential diagnosis, and confirm the histological findings with appropriate immunohistochemical staining. After identifying myopericytoma, it should be treated with wide surgical excision to prevent local recurrence.